Giberellins effect’s at differetn doses on Passiflora edulis Sims seed with two storage times. - Miranda-Barrios, Elizabeth Antonia (2023)
Passion fruit is a versatile fruit, whose demand is increasing by the change in consumer habits. Due to the small knowledge about the process of sexual propagation, the research had as a goal to determine the best concentration of gibberellins in the germination of Passiflora edulis Sims and its effect on seeds with two different storage times. The investigation was by 45 days and were evaluated: germination percentage (PG), mean germination speed (VMG), root length and plant mass. The best results were observed when the sedes have 6 months of storage time and is soaked in gibberellins at 1000 ppm; when the seed has 0 months of storage time, the results are statistically similar at 1000, 1500 and 2000 ppm.